A case of hereditary motor and sensory neuropathy type IVA with unusual genealogy - S. A. Kurbatov; T. B. Milovidova; V. P. Fedotov; A. F. Murtazina; G. E. Rudenskaya; O. A. Shchagina; A. V. Polyakov (Нервно-мышечные болезни)
Background. Hereditary motor and sensory neuropathies (HMSN) are a genetically diverse group of disorders of the peripheral nerves characterized by gradual development of weakness, muscular hypo-/atrophy, sensory disturbances in distal areas of the extremities. Currently among the recessive forms, the most prevalent HMSN is associated with the ganglioside-induced differentiation associated-protein 1 (GDAP1) gene (GDAP1-HMSN).The objective is to present an observation of a family case of HMSN type IVA with unusual genealogy.Materials and methods. Clinical, electrophysiological, and genetic characteristics of a Russian family with GDAP1-HMSN were examined.Results. We describe a family with autosomal recessive HMSN and unusual genealogy due to homozygous and compound heterozygous mutations of GDAP1.Conclusion. The particularity of the described family case is the unusual genealogy with the patients in two non-consecutive generations. This type of inheritance is caused by presence of mutations in compound heterozygous state in the proband's grandson which was confirmed by genetic analysis. The presented case demonstrates the importance and necessity of full analysis of the GDAP1 gene or identification of 2 mutations in trans-position in the proband and subsequent assessment of possible risks for future generations. Multiple stroke-like episodes in the 2 affected members of the family are described that have not been previously reported for GDAP1-HMSN. Stroke has been presented in HMSN associated with mitofusin-2 gene which also as GDAP1, affects mitochondrial function in the neurons.